The Differences of the Prevalences and Serotypes of Dengue Virus on Aedes Aegypti Mosquitoes from Pagutan and Pagutan Timur in the Sub District of Mataram - Nurul Inayati; Supargiyono -; Sitti Rahmah Umniyati (Pusat Kedokteran Tropis, 2012)
Introduction: Sub district of Mataram is one of endemic area of Dengue Haemoraghagic Fever in the West of Nusa Tenggara province, the number of dengue cases are reported increasing every years. Pagutan is a village that has been reported as higth case incidance area and Pagutan Timur as low case insidance area.Objectives: The aims of this study is to determine the density of the Aedes aegypti mosquitoes and to know the prevalence and dominant serotypes of dengue virus in the Aedes aegypti mosquitoes from the village of Pagutan and Pagutan Timur Mataram sub district.Methods: The Collection of Aedes aegypti mosquitoes were conducted by ovitrap provided indoor and outdoor of randomly selected houses. The mosquitoes density was determined by calculating the average number of mosquitoes emerged from eggs collected each houses. The prevalence of dengue virus were calculated by the percentage of mosquitoes that containing of dengue virus as examined by immunocytochemistry method, using the monoclonal antibody anti-dengue DSSE10, while dengue virus serotypes determined by Reverse Transcriptase-Polymerase Chain Reaction using Lanciotti specific primers.Results: The density of Aedes aegypti mosquitoes from Pagutan is significantly higher than Pagutan Timur Village (p<0.05). The confirmed statistical analysis with Paired t test were obtained. The prevalence of dengue virus in Pagutan and Pagutan Timur are 18.4% and respectively 14.3%. The serotypes of dengue virus in Pagutan areas is dengue 1, dengue 2 and dengue 3, whereas in Pagutan Timur areas is dengue 1.Conclusion: There is diffences of mosquitoes density, prevalence and the serotypes of dengue virus found in Aedes aegypti mosquitoes from Pagutan and Pagutan Timur in the sub district of Mataram.Keywords: Mosquito density, Aedes aegypti, dengue virus, prevalence and serotype